Cochlear Response Telemetry: Intracochlear Electrocochleography via Cochlear Implant Neural Response Telemetry Pilot Study Results. Issue 3 (March 2015) - Campbell, Luke; Kaicer, Arielle; Briggs, Robert; O'Leary, Stephen
Abstract : Aim: To record cochlear responses to acoustic stimulation (electrocochleography) directly from a cochlear implant (CI) in awake recipients with residual hearing, using an adaptation of Neural Response Telemetry (NRT) that achieves a 10-ms recording window. Background: Modern cochlear implants contain circuitry for recording neural responses to electrical stimulation, which is known in Cochlear Ltd systems as NRT. We adapted NRT to achieve an extended recording window long enough to record an acoustic electrocochleogram. This paper reports recordings made with this system in recipients with residual hearing. Methods: Subjects were adults with CI422 CIs who retained audiometric thresholds between 75 and 90 dB HL at 500 Hz in their implanted ear. The CI was interfaced to a laptop via a Freedom speech processor connected by USB. Calibrated acoustic stimuli (clicks and tone bursts between 500 and 1, 500 Hz) were presented via insert tube phones to the implanted ear. Responses were acquired through the adapted NRT system. Recordings were made from apical, mid-array, and basal electrodes. Electrocochleography responses were compared with audiometric thresholds. Results: Electrocochleography could be recorded from all five subjects. The compound action potential, cochlear microphonic, and summating potentials were identified. Good quality recordings were most reliably attained from apical electrodes using 40 to 100 repetitions. Audiometric thresholds were similar to compound action potential thresholds. Conclusions: Intracochlear responses to acoustic stimulation can be recorded directly from the CI in awake recipients with residual hearing. This may prove useful for monitoring postoperative hearing and for device fitting.